Beyond forests in the Amazon: biogeography and floristic relationships of the Amazonian savannas - Devecchi, Marcelo F; Lovo, Juliana; Moro, Marcelo F; Andrino, Caroline O; Barbosa-Silva, Rafael G; Viana, Pedro L; Giulietti, Ana Maria; Antar, Guilherme; Watanabe, Maurício T C; Zappi, Daniela C (Botanical journal of the Linnean Society, 2020)
Open habitats such as grasslands occupy < 5% of the Amazon and are currently grouped under the broad term Amazonian savanna, covering an area of c. 267 000 km2, mostly in Brazil and Bolivia. These habitats are found isolated within an extensive rainforest matrix, having a distinct flora from the latter. The lower Amazon River is home to several patches of savanna that occupy both south and north banks of the river, in Santarém, Alenquer and Monte Alegre. Although having an abundance of herbaceous plants, most studies on these open areas focus only on tree species, ignoring the relevant non-woody component of the vegetation. Our objectives were to provide new surveys of seed plants for two Amazonian savanna sites and to take the opportunity to revisit the biogeographical links between Amazonian savanna, Amazonian canga vegetation and the central Brazilian cerrado (CBC) and caatinga, analysing woody and herbaceous plants. We created a floristic database that includes sites of Amazonian savannas, including campinarana, coastal scrub (restinga), CBC and Amazonian campos rupestres (on canga or other substrate). We compared those sites using multivariate analyses to find out the degree of floristic resemblance between sites. We prepared a new list of 406 species of seed plants [336 in Parque Estadual de Monte Alegre (PEMA) and 117 in Serra do Itauajuri (SI)], including 23 new records for the state of Pará and some putative new species for science. The Amazonian savannas form three loosely arranged groups, whereas the Amazonian canga formed a cohesive assemblage. Both groups were contrasted against cerrado and caatinga sites and had a distinctive flora from both. Sites from north-western Pará (Alter do Chão, PEMA and SI) were grouped with their northern counterparts in Roraima. An improved representation of the flora of these sites is provided, with more insight into the relationship between the Amazonian savanna sites and other vegetation types. It is worrying that recent changes of the Brazilian legislation place open environments, such as PEMA, in the path of vulnerability to disturbance and destruction.